Stakeholders' views towards plastic restriction policy in China: Based on text mining of media text. (December 2021) - Kang, Ailin; Ren, Lijun; Hua, Chunyu; Dong, Miaoxin; Fang, Zhaotong; Zhu, Mengyuan
Graphical abstract: Highlights: LDA topic model is used to analyze the stakeholders' views based on news texts. The production capacity of plastic alternatives cannot meet with consumption. National standards for plastic substitutes urgently need to be improved. Opaque information hinders the process of material recycling. Abstract: With the massive use of plastic products, plastic pollution has increasingly attracted worldwide attention. To deal with the problem of plastic pollution, the Chinese government issued the " Opinions on Further Strengthening the Control of Plastic Pollution " (Abbreviated as OFSCPP), which is known as "plastic restriction policy" by the public, in January 2020. It stipulates the timetable and main tasks for restricting the production, sales, and use of certain plastic products, such as plastic bags, disposable straws and agricultural mulch. Since the policy was officially implemented on January 1, 2021, people's lives in China have been considerably affected, and it has also attracted widespread attention from news media. In this study, 310 pieces of news items and information about the OFSCPP published in the first quarter of 2021 from the Baidu News website from which 44, 94, 90, 26, and 49 statements from producers, retailers, consumers, managers, and experts were extracted. The extracted words and expressions were then analyzed using the Latent Dirichlet Allocation topic model. Text analysis results showed that the production efficiency of plastic substitutes in China cannot meet market demand, consumers' experience on plastic substitutes is poor, and recycling and disposal processing information is opaque. To achieve the policy goals, the government should encourage the innovation of high-quality and inexpensive plastic alternatives, the national standards for plastic substitutes should be urgently improved, consumers' concept of green consumption should be gradually cultivated, and terminal recycling and disposal should be promoted.